Machine learning and deep learning techniques for medical science - Gayathri Devi, K. G. (Boca Raton : CRC Press, 2022)
"This book presents the integration of machine learning and deep learning algorithms that can be applied in the healthcare sector to reduce the time needed by doctors, radiologists, and other medical professionals to analyze, predict, and diagnose conditions with accurate results"--
OCLC-licensed vendor bibliographic record.
Keywords: Medical informatics; Machine learning; Deep learning (Machine learning); Artificial intelligence -- Medical applications; Medical technology